2022
DOI: 10.3390/polym14153199
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Application in Packaging Grease of Gelatin–Sodium Alginate Edible Films Cross-Linked by Pullulan

Abstract: Gelatin–sodium alginate-based edible films cross-linked with pullulan were prepared using the solution casting method. FTIR spectroscopy demonstrated the existence of hydrogen bonding interactions between the components, and scanning electron microscopy observed the component of the films, revealing electrostatic interactions and thus explaining the differences in the properties of the blend films. The best mechanical properties and oxygen barrier occurred at a 1:1 percentage of pullulan to gelatin (GP11) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Probably the antioxidant activity of the produced films is related to the presence of pullulan. Li et al (2022) observed a DPPH radical scavenging rate of 9.24% by pure pullulan. It also found that when adding pullulan to gelatin films, there was an increase in its antioxidant activity.…”
Section: Assessment Of Antioxidant Activitymentioning
confidence: 94%
“…Probably the antioxidant activity of the produced films is related to the presence of pullulan. Li et al (2022) observed a DPPH radical scavenging rate of 9.24% by pure pullulan. It also found that when adding pullulan to gelatin films, there was an increase in its antioxidant activity.…”
Section: Assessment Of Antioxidant Activitymentioning
confidence: 94%
“… 17 Transglutaminase is a cross-linked enzyme that catalyses the formation of isopeptide bonds between protein molecules, so it has potential applications to improve physicochemical properties such as solubility, water holding capacity, and emulsifying ability of protein-based edible films or coatings. 18 Among these, the chemical method is considered a popular method due to the variety of additives including hydrocolloids (xanthan gum, 15 oxidized guar gum, 19 tara gum/locust bean gum, 20 and gum tragacanth/locust bean gum 21 ) as copolymers or alginate dialdehyde 22 and pullulan 23 as cross-linking agents. There are many studies using different hydrocolloids to modify the structure and mechanical properties of gelatin-based films; for example, gelatin-based films modified by CMC/xanthan gum has been improved in terms of water vapor permeability, UV blocking, thermal stability and tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its high-stability thickening and gelling characteristics and excellent properties such as biocompatibility, biodegradability, immunogenicity, antibacterial activity, hydrophilicity, and non-toxicity, alginate is considered an important industrial polysaccharide. Therefore, AG is applied in various fields, including food, packaging, composites, cosmetics, textile printing, medicine, biomaterials, and pharmaceuticals [16][17][18][19][20]. Carrageenan is a linear sulfated polysaccharide and a major constituent of red edible seaweeds.…”
Section: Introductionmentioning
confidence: 99%